2016
DOI: 10.1111/pim.12391
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the development of subunit vaccines for gastrointestinal nematodes of ruminants

Abstract: SummaryThe global increase in anthelmintic resistant nematodes of ruminants, together with consumer concerns about chemicals in food, necessitates the development of alternative methods of control for these pathogens. Subunit recombinant vaccines are ideally placed to fill this gap. Indeed, they are probably the only valid option for the long-term control of ruminant parasitic nematodes given the increasing ubiquity of multidrug resistance in a range of worm species across the world. The development of a subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 105 publications
1
65
0
Order By: Relevance
“…Several recombinant vaccine antigens, expressed in Escherichia coli , insect cells, Pichia pastoris or the free‐living nematode Caenorhabditis elegans , failed to confer protection in vaccine trials (Cachat, Newlands, Ekoja, McAllister, & Smith, ; Geldhof, Meyvis, Vercruysse, & Claerebout, ; Roberts et al., ; Vlaminck et al., ). Current research is focusing on differences in protein folding or secondary modifications, such as glycosylation, between the native and recombinant proteins as possible reasons for the lack of protection (Matthews et al., ). Recently, a number of recombinant vaccines showed promising results.…”
Section: Main Means Of Detection Prevention and Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recombinant vaccine antigens, expressed in Escherichia coli , insect cells, Pichia pastoris or the free‐living nematode Caenorhabditis elegans , failed to confer protection in vaccine trials (Cachat, Newlands, Ekoja, McAllister, & Smith, ; Geldhof, Meyvis, Vercruysse, & Claerebout, ; Roberts et al., ; Vlaminck et al., ). Current research is focusing on differences in protein folding or secondary modifications, such as glycosylation, between the native and recombinant proteins as possible reasons for the lack of protection (Matthews et al., ). Recently, a number of recombinant vaccines showed promising results.…”
Section: Main Means Of Detection Prevention and Controlmentioning
confidence: 99%
“…For example, it has been suggested that a reduction of cumulative FEC by around 60% during the first 2 months after turnout would sufficiently reduce pasture infection levels to protect young stock against O. ostertagi and C. oncophora until the end of the grazing season (Claerebout, Knox, & Vercruysse, ). However, this hypothesis is based on the assumption that a typical first grazing season in Western Europe lasts for about 6 months, and vaccine efficacy requirements are likely to be different in regions with continuous grazing throughout the year, such as parts of South America and New Zealand (Matthews et al., ). Vaccine efficacy requirements may also be different in calves or lambs that co‐graze with their dams.…”
Section: Main Means Of Detection Prevention and Controlmentioning
confidence: 99%
“…However, it is unlikely that these vaccines will achieve a greater than 90 per cent reduction in egg counts and, as a consequence, whole-flock strategies are still necessary (Matthews and others 2016). …”
Section: Haccp: Risk-based Pge Management Planningmentioning
confidence: 99%
“…1 Vaccines are considered a favorable option, because of the durable protection they can provide and a lack of chemical residues in animal products and the environment. 2 The principle of vaccination is to induce immunologic protection in a host against a subsequent infection. For this, the immune system can be stimulated with either the weakened or killed pathogen or proteins/antigens from it, the so-called subunit vaccines ( Fig.…”
Section: Introductionmentioning
confidence: 99%